2014
DOI: 10.1002/dmrr.2577
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin levels are lower in premenopausal women with type 1 diabetes mellitus compared with matched controls

Abstract: Background Oxytocin (OT), a hormone most commonly associated with parturition and lactation, may have additional roles in diabetes complications. We determined OT levels in premenopausal women with type 1 diabetes mellitus (T1DM) compared to nondiabetic controls; and examined associations of OT with health behaviors, clinical factors, biomarkers, kidney function, and bone health. Lower OT was hypothesized for T1DM. Methods Cross-sectional study of premenopausal women with T1DM (n=88) from the Wisconsin Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Similarly, intranasal oxytocin administration to obese and prediabetic patients resulted in a significant decrease of body weight after 4 and 8 weeks of treatment [20]. In line with these evidences, cohort studies investigating oxytocin concentration additionally found an inverse association between oxytocin and obesity, HbA1C levels, insulin resistance as well as T1DM or T2DM, thus emphasizing the potential negative influence of positive energy states on circulating oxytocin [21,22,23]. However, this inference has been recently challenged in a study in premenopausal women with different energy states [24].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Similarly, intranasal oxytocin administration to obese and prediabetic patients resulted in a significant decrease of body weight after 4 and 8 weeks of treatment [20]. In line with these evidences, cohort studies investigating oxytocin concentration additionally found an inverse association between oxytocin and obesity, HbA1C levels, insulin resistance as well as T1DM or T2DM, thus emphasizing the potential negative influence of positive energy states on circulating oxytocin [21,22,23]. However, this inference has been recently challenged in a study in premenopausal women with different energy states [24].…”
Section: Introductionmentioning
confidence: 57%
“…Complimentarily, oxytocin levels have been found decreased in most but not all animal models of obesity and T2DM, including diet-induced-obesity (DIO) and carriers of leptin deficiency [16,36,37]. In cohort studies, oxytocin levels are reportedly similar between genders [22] as well as with regard to decline with age [38], and decrease in obesity and newly diagnosed T2DM [23]. Concordant with evidence that estrogen loss decreases oxytocin levels, our current results show that oxytocin levels are lower in postmenopausal than premenopausal women both in normal-weight and obese conditions, suggesting that an inverse association relates oxytocin to menopause independently of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men and women with type 2 diabetes mellitus 92 and women with type 1 diabetes mellitus 115 have been shown to have lower levels of oxytocin than controls. Furthermore, in those with type 2 diabetes mellitus, low fasting levels of oxytocin were associated with higher levels of glucose and insulin, both after fasting and after an oral glucose tolerance test, as well as higher HOMA-IR results and levels of HbA 1c 92 ; these findings suggest that diabetes mellitus could be a state of oxytocin deficiency.…”
Section: Glucose Homeostasismentioning
confidence: 99%
“…In a large sample of men with metabolic syndrome, oxytocin concentrations were elevated compared with healthy controls, whereas the obese subjects of the present experiment displayed lower baseline oxytocin levels than their lean counterparts. Decreased oxytocin concentrations were reported in patients with metabolic syndrome or diabetes mellitus, suggesting a certain degree of oxytocin deficiency in diabetic patients . However, our preliminary finding of a positive relationship between HOMA‐IR and baseline oxytocin concentrations in the obese subjects argues against this assumption.…”
Section: Discussionmentioning
confidence: 68%